Fully Magnetically Levitated Left Ventricular Assist System for Treating Advanced HF: A Multicenter Study - Netuka, Ivan; Sood, Poornima; Pya, Yuriy; Zimpfer, Daniel; Krabatsch, Thomas; Garbade, Jens; Rao, Vivek; Morshuis, Michiel; Marasco, Silvana; Beyersdorf, Friedhelm; Damme, Laura; Schmitto, Jan D (Journal of the American College of Cardiology, 2015)
BACKGROUND: The HeartMate 3 left ventricular assist system (LVAS) is intended to provide long-term support to patients with advanced heart failure. The centrifugal flow pump is designed for enhanced hemocompatibility by incorporating a magnetically levitated rotor with wide blood-flow paths and an artificial pulse. OBJECTIVES: The aim of this single-arm, prospective, multicenter study was to evaluate the performance and safety of this LVAS. METHODS: The primary endpoint was 6-month survival compared with INTERMACS (Interagency Registry for Mechanically Assisted Circulatory Support)-derived performance goal. Patients were adults with ejection fraction ≤ 25%, cardiac index ≤ 2.2 l/min/m(2) without inotropes or were inotrope-dependent on optimal medical management, or listed for transplant. RESULTS: Fifty patients were enrolled at 10 centers. The indications for LVAS support were bridge to transplantation (54%) or destination therapy (46%). At 6 months, 88% of patients continued on support, 4% received transplants, and 8% died. Thirty-day mortality was 2% and 6-month survival 92%, which exceeded the 88% performance goal. Support with the fully magnetically levitated LVAS significantly reduced mortality risk by 66% compared with the Seattle Heart Failure Model-predicted survival of 78% (p = 0.0093). Key adverse events included reoperation for bleeding (14%), driveline infection (10%), gastrointestinal bleeding (8%), and debilitating stroke (modified Rankin Score > 3) (8%). There were no pump exchanges, pump malfunctions, pump thrombosis, or hemolysis events. New York Heart Association classification, 6-min walk test, and quality-of-life scores showed progressive and sustained improvement. CONCLUSIONS: The results show that the fully magnetically levitated centrifugal-flow chronic LVAS is safe, with high 30-day and 6-month survival rates, a favorable adverse event profile, and improved quality of life and functional status. (HeartMate 3™ CE Mark Clinical Investigation Plan [HM3 CE Mark]; NCT02170363).
Keywords: Heart Transplantation; Equipment Design; Stroke Volume; Female; Heart Ventricles; kardiotonika; thrombosis; pump; výsledek terapie; ženské pohlaví; srdeční komory; Heart Failure; Hemodynamics; Heart-Assist Devices; hemodynamika; lidé; srdeční selhání; Survival Analysis; HeartMate 3; Treatment Outcome; Long-Term Care; stupeň závažnosti nemoci; prospektivní studie; Male; podpůrné srdeční systémy; Aged; Prospective Studies; tepový objem; dlouhodobá péče; transplantace srdce; analýza přežití; Cardiotonic Agents; quality of life; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; design vybavení; Middle Aged; hemolysis; Humans